DEVELOPING CRITICAL READING THROUGH TEXTUAL ANALYSIS TO PROMOTE DEMOCRATIC DISCOURSE: A STUDY ON ENGLISH EDUCATION STUDENTS - Yuliarsih, Yuliarsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study explores the development of critical reading skills through textual analysis to promote democratic discourse among English Education students at FKIP Universitas Madura. In the context of the post-truth era, where misinformation challenges rational communication, critical literacy is essential for nurturing democratic competencies. This qualitative descriptive research involved 25 fifth-semester students and employed classroom observations, written responses, and semi-structured interviews to collect the data. The analysis focused on students’ abilities to interpret texts, evaluate arguments, and reflect ideologically. The findings reveal a significant improvement in students’ critical reading competencies, as they increasingly identify central themes, authorial intentions, and social contexts within texts. Moreover, the students demonstrated heightened awareness of bias, intertextuality, and hegemonic values embedded in media narratives. These competencies were manifested in both written assignments and class discussions, where the students engaged in deliberative dialogues marked by tolerance, respect, and rational argumentation. The study confirms that textual analysis is an effective pedagogical approach for integrating language skills with civic literacy, fostering not only the cognitive but also the affective and ethical dimensions of reading. The implications include the necessity for teacher training in critical literacy and the incorporation of democratic education principles into the English curriculum. Future research could explore long-term interventions and the integration of digital literacy to further enhance students’ critical engagement with texts across various media. ABSTRAK Penelitian ini mengeksplorasi pengembangan keterampilan membaca kritis melalui analisis tekstual untuk mempromosikan wacana demokrasi di kalangan mahasiswa Pendidikan Bahasa Inggris di FKIP Universitas Madura. Dalam konteks era pasca-kebenaran, di mana informasi yang salah menantang komunikasi rasional, literasi kritis sangat penting untuk memelihara kompetensi demokrasi. Penelitian deskriptif kualitatif ini melibatkan 25 mahasiswa semester lima dan menggunakan observasi kelas, tanggapan tertulis, dan wawancara semi-terstruktur untuk mengumpulkan data. Analisis berfokus pada kemampuan siswa untuk menafsirkan teks, mengevaluasi argumen, dan merefleksikan secara ideologis. Temuan ini mengungkapkan peningkatan yang signifikan dalam kompetensi membaca kritis siswa, karena mereka semakin mengidentifikasi tema sentral, niat penulis, dan konteks sosial dalam teks. Selain itu, para siswa menunjukkan kesadaran yang tinggi akan bias, intertekstualitas, dan nilai-nilai hegemonik yang tertanam dalam narasi media. Kompetensi ini diwujudkan baik dalam tugas tertulis maupun diskusi kelas, di mana siswa terlibat dalam dialog deliberatif yang ditandai dengan toleransi, rasa hormat, dan argumentasi rasional. Studi ini menegaskan bahwa analisis tekstual adalah pendekatan pedagogis yang efektif untuk mengintegrasikan keterampilan bahasa dengan literasi sipil, menumbuhkan tidak hanya dimensi kognitif tetapi juga dimensi afektif dan etis membaca. Implikasinya termasuk perlunya pelatihan guru dalam literasi kritis dan penggabungan prinsip-prinsip pendidikan demokratis ke dalam kurikulum bahasa Inggris. Penelitian di masa depan dapat mengeksplorasi intervensi jangka panjang dan integrasi literasi digital untuk lebih meningkatkan keterlibatan kritis siswa dengan teks di berbagai media.